Following the Money: The Wire and Distant American Studies - Sven Cvek ([sic])
In this essay, I argue that the pedagogical, or, more generally, heuristic potential of HBO’s crime drama The Wire (2002/2008) is related to the specific institutional developments in post-network television, the show’s didactic intention, and its focus on the delineation of the economic process, or what has been called its “openly class-based” politics. I will dedicate most time to the latter, as it represents a particularly welcome intervention for American Studies, a discipline in which the problem of class has usually been either marginalized, or articulated in terms of the historically hegemonic disciplinary paradigm, that of identityKeywords: The Wire, American studies, cognitive mapping, capitalism, TV, HBOIn this essay, I would like to approach HBO’s crime drama The Wire (2002-2008) based on my experience of teaching the show in an American Studies class in Croatia. The course in which I try to work with it, Cultural Aspects of American Neoliberalism, deals with the gradual departure in the US from the legacy of the New Deal, with a special focus on the cultural articulations of economic inequality from the 1970s onwards. Using The Wire in the classroom is nothing new. It has been taught for years now in different courses, mostly in the US. A quick web search will show that it has appeared in curricula in film studies, media studies, urban studies, ethics, communication, criminal justice, sociology, social anthropology, and social work. The inclusion of the series in these various academic fields seems to confirm what I have learned from experience: the show offers plenty of teachable material. Moreover, the variety of pedagogical uses of The Wire speaks to the series’ ability to serve many different disciplinary interests, both in the US and abroad. Here, I would like to make a point precisely out of the apparent potential of The Wire to provide a common ground for the recognition of a diverse array of particular social positions and experiences.